Yogurt enrichment with Spirulina (Arthrospiraplatensis): effect on physicochemical, textural properties and consumers acceptance - Debbabi H.; Boubaker B.; Gmati T.; Chouaibi M.; Boubaker A.; Snoussi A. (Innovation for sustainability in sheep and goats, 2019)
CyanobacteriumSpirulina (Arthrospiraplatensis) is a filamentous multicellular, blue-green microalgae, known for its balanced biochemical composition (good quality proteins, balanced fatty acid profiles, vitamins, antioxidants and minerals). Moreover, since 1981, Food and Drug Administration has considered it as “generally recognized as safe” (GRAS) and recommends a consumption at a level up to 300 mg/kg body/day, when dried. Therefore this makes it interesting to incorporate into the formulation of novel functional products. The objective of the study was to develop a functional yogurt enriched with Spirulina. Spirulina powder (0.1-0.5 % of milk) was added to the standardized pasteurized milk, prior to lactic fermentation during manufacturing process. Physicochemical, textural and sensory properties were assessed. Preliminary formulations indicated that addition into yogurt of Spirulina powder in concentrations above to 0.3% of milk led to a weaker sensory acceptability. However, flavouring with vanilla/mint aromas has improved overall acceptability. Additional formulations showed that the incorporation of 0.12 and 0.24% resulted in a significant increase in proteins (up to +46%) and minerals contents (up to +23%) and in calorie value (up to +80%), but did not affect pH and syneresis. A higher curd strength was observed with 0.24%Spirulina-enriched product. Sensory quality was not affected by incorporating Spirulina up to 0.24% into yogurt. In conclusion the incorporation of Spirulina powder can enhance the nutritional quality of yogurt, without affecting its sensory properties.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)